PERENCANAAN PEGAWAI, KUALITAS PEGAWAI, EFEKTIVITAS KERJA, LINGKUNGAN FISIK DAN KINERJA PEGAWAI - Sri Retno Haswati (Jurnal Manajemen dan Bisnis, 2013)
In Indonesia, for the past few years, the state revenue from tax sector have a reallysignificant role in the state funding. So, it is only logical that Directorate General of Taxationas the part of the government that officially responsible for the collection of tax revenue needto perfom it’s fucntions at the best it can be. Directorate General of Taxation just as allothers organizations needed human resources as the driver of it’s performance. So in orderto perform it’s functions at the best it can be, Directorate General of Taxation needed thebest human resources it can recruit. Gianyar Tax Office as a part of Directorate General ofTaxation is holding the functions to provide information, deliver services and controllingabout taxation. To perform it’s functions Gianyar Tax Office need to manage it’s humanresouces so they can perform their duty as the driver of the office performance. In practice,there’s a gap between the condition expected and the reality.The purpose of the research is to know, learn and proving the effect of humanresources planning, employee quality, work effectiveness to human resources performance atGianyar Tax Office.The research was a population research. Population of the research was all thegovernment officials of Gianyar Tax Office with 86 officials but only 81 were participat in.Data gathering is done by using questionnaire, observation and documentation at thelocation of the research, which is Gianyar Tax Office. Data analize is done by using SEM.The reseach result showed that there is 78,5% positif influence of human resourcesplanning to employee quality, there is 92,2% positif influence of human resource planning,physical working enviroment and employee quality to working effectiveness, and there is94,6% positif influence of human resource planning, physical working enviroment, employeequality, working effectiveness to employee performance.Keywords : employee performance, human resources management, Structural Equation Modelling